Clinical and radiographic predictors of the need for inferior vena cava resection during nephrectomy for patients with renal cell carcinoma and caval tumour thrombus. (23rd March 2015) - Psutka, Sarah P.; Boorjian, Stephen A.; Thompson, Robert H.; Schmit, Grant D.; Schmitz, John J.; Bower, Thomas C.; Stewart, Suzanne B.; Lohse, Christine M.; Cheville, John C.; Leibovich, Bradley C.
<x xml:space="preserve">Abstract</x> Objective To evaluate the clinical and radiographic predictors of the need for partial or circumferential resection of the inferior vena cava (IVC) requiring complex vascular reconstruction during venous tumour thrombectomy for renal cell carcinoma (RCC). Patients and Methods Data were collected on 172 patients with RCC and IVC (levels I–IV) venous tumour thrombus who underwent radical nephrectomy with tumour thrombectomy at the Mayo Clinic between 2000 and 2010. Preoperative imaging was re‐reviewed by one of two radiologists blinded to details of the patient's surgical procedure. Univariable and multivariable associations of clinical and radiographic features with IVC resection were evaluated by logistic regression. A secondary analysis was used to assess the ability of the model to predict histological invasion of the IVC by the tumour thrombus. Results Of the 172 patients, 38 (22%) underwent IVC resection procedures during nephrectomy. Optimum radiographic thresholds were determined to predict the need for IVC resection based on preoperative imaging included a renal vein diameter at the renal vein ostium (RVo) of 15.5 mm, maximum anterior–posterior (AP) diameter of the IVC of 34.0 mm and AP and coronal diameters of the IVC at the RVo of 24 and 19 mm, respectively. On multivariable analysis, the presence of a right‐sided tumour (odds ratio 3.3; P = 0.017), an AP diameter of the IVC at the RVo of ≥24.0 mm (odds ratio 4.4; P = 0.017), and radiographic identification of complete occlusion of the IVC at the RVo (odds ratio 4.9; P < 0.001) were associated with a significantly increased risk of IVC resection. The c‐index for the model was 0.81. Conclusions We present a multivariable model of the radiographic features associated with the need for IVC resection during tumour thrombectomy. Pending external validation, this model may be used for preoperative planning, patient counselling and planned involvement of vascular surgical colleagues in anticipation of the need for complex vascular repair.